1998
DOI: 10.1007/s004649900785
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy under epidural anesthesia in patients with chronic respiratory disease

Abstract: LC can be performed safely under epidural anaesthesia in patients with severe COPD. Intraoperative shoulder tip or abdominal pain does not seem to be a major deterrent and can be effectively controlled with small doses of opioid analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 15 publications
2
89
1
6
Order By: Relevance
“…The blood pressure and heart rate remained stable during the procedure [8]. Pursnani et al reported in his study of laparoscopic cholecystectomy performed under TEA in patients with chronic respiratory disease that all patients under thoracic epidural anaesthesia had no change in their cardio-respiratory status all over the procedure [9]. The present study did not detect any significant differences between the baseline and 5-minutes intervals within the first hour of surgery in the two groups as regard O 2 saturation measured by pulse oximetry.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The blood pressure and heart rate remained stable during the procedure [8]. Pursnani et al reported in his study of laparoscopic cholecystectomy performed under TEA in patients with chronic respiratory disease that all patients under thoracic epidural anaesthesia had no change in their cardio-respiratory status all over the procedure [9]. The present study did not detect any significant differences between the baseline and 5-minutes intervals within the first hour of surgery in the two groups as regard O 2 saturation measured by pulse oximetry.…”
Section: Resultsmentioning
confidence: 94%
“…Thoracic epidural anaesthesia (TEA) has been consistently shown to provide excellent pain relief, to facilitate early ambulation. Many used regional anaesthesia alone for laparoscopic cholecystectomy in patients with chronic obstructive airway disease [4,8,9]. It has been also used in other studies, alone for laparoscopic cholecystectomy in healthy patients [4,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the anesthetic technique should be tailored to the type of surgery. General anesthesia (balanced anesthesia technique with several intravenous and inhalational agents and the use of muscle relaxants), peripheral nerve blocks, and neuraxial anesthesia as an alternative to general anesthesia for outpatient pelvic laparoscopy, local anesthesia infiltration in microlaparoscopy for limited and precise gynecological procedures, and intravenous sedation can be used with a safe profile for patients and have been described in the literature (LE 5) [364], (LE 4) [365], (LE 2b) [366,367], (LE 1b) [368], (LE 1a) [369], (LE 4) [370], (LE 1b) [371,372], (LE 2b) [373,374], (LE 1b) [375]. Laparoscopy is most commonly performed with the patient under general anesthesia, especially for prolonged and upper abdominal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…general anesthesia (GA), a gold-standard anesthetic technique. 3 For the both procedures but, it can be extremely challenging for patients with difficult intubation, obstructive pulmonary.…”
Section: Introductionmentioning
confidence: 99%